Legal Implications of Consumer Personal Data Misuse by OJK Licensed Fintech Lending Operators - Tektona, Rahmadi Indra (Arena Hukum, 2024)
The Financial Services Authority (OJK) has released a list of registered and licensed fintechs. The Investment Alert Task Force has taken firm action against illegal fintech lending that has the potential to break the law, along with the Indonesian National Police and the Ministry of Communication and Information. Privacy is violated when personal data are collected and shared. In the misuse of fintech lending consumer personal data, consumer rights are violated, and the loss is in the form of immaterial compensation. The legal implications are not only legal consequences with violations committed by the organizer, which result in the imposition of sanctions by the state. This normative legal research uses statutory, conceptual, and comparative approaches with a deductive-analytical method to explain the importance of regulating of personal data consumer protection on fintech lending operators.